Pulmonary root remodeling procedure for symptomatic supravalvular pulmonary stenosis in an adult patient who underwent pulmonary artery banding: a case report - Kei Mukawa; Yutaka Iba; Nobuyoshi Kawaharada (BMC Cardiovascular Disorders)
Abstract Background Pulmonary artery banding (PAB) is performed as a palliative surgery for congenital heart diseases. Although pulmonary stenosis is one of the complications of PAB, symptomatic supravalvular pulmonary stenosis (SVPS) in adulthood after PAB is an extremely rare condition. Further, very few studies have focused on surgical cases of SVPS in adult. Herein, we describe a case of symptomatic SVPS in adulthood after PAB that was successfully managed with surgery. Case presentation A 55-year-old male patient had been presenting with worsening shortness of breath for 10 years. Of note, he had been diagnosed with membranous ventricular septum defect at birth and he underwent PAB at 11 months of age. The patient underwent direct closure of ventricular septum defect and pulmonary artery debanding at 3 years and 6 months old. Medical examinations showed SVPS, with a pressure gradient of 60 mmHg. We planned pulmonary artery anterior wall plasty. However, based on the operative findings, the pulmonary stenosis was located in the whole circumference just above the annulus. Hence, it was challenging to completely relieve the stenosis with a pulmonary patch, and the Yacoub remodeling technique was applied to pulmonary artery reconstruction. Intraoperative pressure gradient between the right ventricle and the distal pulmonary artery dropped to 11 mmHg. Post operative course was uneventful. Conclusions Patient with SVPS could present with symptoms in the long term after PAB in childhood. Therefore, due to the currently increasing number of adult congenital heart disease (ACHD) cases, attention should be paid to patients who underwent PAB. In this case, pulmonary artery was degenerated in the whole circumference because of the remained banding tape and the stenosis part was just above the annulus. Therefore, we applied Yacoub remodeling technique to this reconstruction. This pulmonary root remodeling procedure was an effective option for such SVPS.